2017
DOI: 10.1002/dev.21586
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to ketamine in rats: Implications on animal models of schizophrenia

Abstract: Schizophrenia is a complex neuropsychiatric disorder characterized by hallucinations, delusions, anhedonia, flat affect and cognitive impairments. The aim of this study was to propose a prenatal treatment with ketamine, a psychedelic drug that acts as a noncompetitive inhibitor of glutamate NMDA receptors, as a neurodevelopmental animal model of schizophrenia. The drug was applied (i.m. 60 mg.kgSprague-Dawley rats on gestational Day 14. Offspring behavior was studied on pubertal (4 weeks old) and adult (10 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…In humans, schizophrenia is characterized by positive symptoms (e.g., hallucination, delusion), negative symptoms (e.g., loss of motivation, social isolation), and cognitive symptoms (e.g., impairments in attention and memory). Coronel-Oliveros and Pacheco-Calderón (2018) observed that the animals prenatally exposed to ketamine exhibited disinhibition and hyperactive behavior in pubertal stage, and cognitive impairments, social withdrawal, anxiety, depression, and aggressive-like behaviors in adulthood. These schizophrenia-like phenotypes in animals with prenatal ketamine challenge strongly supported the deleterious effects of ketamine on neurobehavioral functions throughout life.…”
Section: Neurotoxicity Of Ketamine To the Developing Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, schizophrenia is characterized by positive symptoms (e.g., hallucination, delusion), negative symptoms (e.g., loss of motivation, social isolation), and cognitive symptoms (e.g., impairments in attention and memory). Coronel-Oliveros and Pacheco-Calderón (2018) observed that the animals prenatally exposed to ketamine exhibited disinhibition and hyperactive behavior in pubertal stage, and cognitive impairments, social withdrawal, anxiety, depression, and aggressive-like behaviors in adulthood. These schizophrenia-like phenotypes in animals with prenatal ketamine challenge strongly supported the deleterious effects of ketamine on neurobehavioral functions throughout life.…”
Section: Neurotoxicity Of Ketamine To the Developing Brainmentioning
confidence: 99%
“…It has been hypothesized that glutamatergic dysfunction may be involved in the etiology of schizophrenia (Moghaddam et al, 1997; Frohlich and Van Horn, 2014), a neuropsychiatric disorder with peak onset periods at late adolescence and early adulthood. In this regard, Coronel-Oliveros and Pacheco-Calderón (2018) has recently proposed an animal model of schizophrenia using rats prenatally exposed to ketamine. In humans, schizophrenia is characterized by positive symptoms (e.g., hallucination, delusion), negative symptoms (e.g., loss of motivation, social isolation), and cognitive symptoms (e.g., impairments in attention and memory).…”
Section: Neurotoxicity Of Ketamine To the Developing Brainmentioning
confidence: 99%
“…Acute ketamine administration in animals results in cognitive deficits including reduced sensorimotor gating, spatial learning and memory impairments, along with changes in theta and gamma band activity (Verma and Moghaddam, 1996; de Bruin et al, 1999; Ehrlichman et al, 2009; Kittelberger et al, 2012; Szlachta et al, 2017; Coronel-Oliveros and Pacheco-Calderon, 2018). In contrast to cortical hypodopaminergic state observed in schizophrenia, these cognitive deficits are accompanied by increased DA release in the PFC (Verma and Moghaddam, 1996).…”
Section: Pharmacological Approaches To Induce Nmdar Hypofunctionmentioning
confidence: 99%
“…Other studies also reported that cognitive deficits are associated with increased frontal cortical blood flow (Ingvar and Franzen, 1974; Vollenweider et al, 1997). Moreover, acute ketamine administration induces hyperlocomotor activity and stereotypic behaviors, which might be attributed to increased DA and serotonin turnover in the striatum and cortex (Irifune et al, 1991; Chatterjee et al, 2011, 2012; Coronel-Oliveros and Pacheco-Calderon, 2018). However, there are inconsistent reports as to the effect of acute ketamine administration on negative symptoms-related behaviors based on social interaction tests (Silvestre et al, 1997; Chatterjee et al, 2011; Coronel-Oliveros and Pacheco-Calderon, 2018).…”
Section: Pharmacological Approaches To Induce Nmdar Hypofunctionmentioning
confidence: 99%
“…The average value was calculated for the number of positive cells: 6 rats per group, one slice per rat per region. 24…”
Section: Nissl Stainmentioning
confidence: 99%